Ответ:
а) (х+7,2)*4,2=30,996
4,2х+30,24=30,996
4,2х=30,996-30,24
4,2х=0,756
х=0,18
б) 9,88/(6,7-х)=2,6
9,88/(6,7-х)=2,6 х ≠ 6,7
/(
- х) = 2,6
![\frac{247}{25} \frac{247}{25}](https://tex.z-dn.net/?f=%5Cfrac%7B247%7D%7B25%7D)
2,6
![\frac{494}{5(67-10х)}=2,6 \frac{494}{5(67-10х)}=2,6](https://tex.z-dn.net/?f=%5Cfrac%7B494%7D%7B5%2867-10%D1%85%29%7D%3D2%2C6)
494=13(67-10х)
38=67-10х
10х=67-38
10х=29
х=
, х ≠6,7
х=
, х≠![\frac{67}{10} \frac{67}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B67%7D%7B10%7D)
х=2,9 (другая форма)
д) 9,14х - (3,78х+2,87х)=12,45
9,14х - 6,65х=12,45
2,49х = 12,45
х=5
Пошаговое объяснение: